Penerapan Pendekatan Problem Posing Berbasis Aktivitas dalam Pembelajaran Fisika di MAN 4 Sukabumi - Rizal Alamsyah (MADRASCIENCE: Jurnal Pendidikan Islam, Sains, Sosial, dan Budaya, 2021)
This research is motivated by the low value of Physics subjects in class X IPA MAN 4 Sukabumi. This study aims to determine the results of learning physics with vibration and wave materials with an activity-based problem posing approach in class X IPA MAN 4 Sukabumi in the 2019/2020 academic year. The method used in this research is the experimental method. The research method chosen was a quasi-experimental design with a pretest-posttest control design. Data collection techniques through tests, observations, and interviews. The results showed that the experimental class using the activity-based problem posing approach had higher learning outcomes than the control class using conventional or lecture methods. This can be seen from the data on student physics learning outcomes after being given treatment. The average value of the experimental class is 84.47, while the average value of the control class is 68.50. The data shows that the physics learning outcomes for students who are given an activity-based problem-posing approach are higher than the physics learning achievements of students who use conventional learning approaches. Thus, an activity-based problem-posing approach needs to be applied in schools to support better learning outcomes.